2018
DOI: 10.1038/s41567-018-0179-8
|View full text |Cite|
|
Sign up to set email alerts
|

Pair-breaking quantum phase transition in superconducting nanowires

Abstract: Quantum phase transitions (QPT) between distinct ground states of matter are widespread phenomena [1][2][3][4][5] , yet there are only a few experimentally accessible systems 6,7 where the microscopic mechanism of the transition can be tested and understood. These cases are unique and form the experimentally established foundation for our understanding of quantum critical phenomena. Here we report that a magnetic-fielddriven QPT in superconducting nanowires-a prototypical one-dimensional system (d= 1)-can be f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Recently, we have found that another 1d system, namely superconducting nanowires, undergoes a QPT when driven by a magnetic field, B . 30 We have also found that the transition can be completely described by the pair-breaking critical theory with only one adjustable parameter, C , in the scaling formula 31…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Recently, we have found that another 1d system, namely superconducting nanowires, undergoes a QPT when driven by a magnetic field, B . 30 We have also found that the transition can be completely described by the pair-breaking critical theory with only one adjustable parameter, C , in the scaling formula 31…”
mentioning
confidence: 78%
“…In this equation, D is the diffusion coefficient, c B critical field, and F a non-universal constant computed from the parameters of nanowires such as cross-sectional area and critical temperature. 30 The scaling function 1σ…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Superconducting fluctuations (SFs) lead to several interesting quantum phenomena such as superconductor-insulator quantum transition (SIT) 1,2 , quantum criticality 3 , phase slip (PS) effects 47 , etc. These quantum phenomena are mainly controlled by sample properties like geometry and dimensions, crystallinity, disorder and inhomogeneity and also by external parameters like electro-magnetic field, driving current, temperature etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a pair-breaking superconductor-metal quantum phase transition has been observed in amorphous Mo-Ge nanowires [60]. In these wires, the disorder turns out to be rather weak and plays no role in the measured temperature range.…”
Section: Discussionmentioning
confidence: 99%